1996
DOI: 10.3109/08923979609052747
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina PlatensisExposure Enhances Macrophage Phagocytic Function in Cats

Abstract: Bronchoalveolar lavage macrophages isolated from cats were cultured on glass coverslips. Macrophages were exposed to a water-soluble extract of Spirulina platensis in concentration range of 0 to 60 micrograms per mL for two hours. Spirulina-extract exposure did not cause significant macrophage cytotoxicity over untreated control cultures. Macrophage monolayers from treated and control cultures were incubated with sheep red blood cells (SRBC) as well as viable Escherichia coli. The percentages of phagocytic mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 6 publications
4
31
0
Order By: Relevance
“…Our results agree with Promya and Chitmant (2011) who reported that fingerlings which received feed 5% A. platensis+ basal diets had higher values for red and white blood cell counts and immunity stimulating capacity. The increase in red and white blood cells and immunity stimulating capacity due to the presence of C-phycocyanin in Spirulina, which can help build the immunity capacity (Vonshak, 1997b).Our results were in agreement with Qureshi et al (1996) who reported that Spirulina could stimulate the immune system via increasing the phagocytic and the natural killer activities and with Bermejo et al (2008) who reported that most antioxidant capacities of Spirulina protein extract are attributable to the biliproteins contained in this microalga, such as phycocyanin so that we can use Spirulina to improve the immunity capacity of the animals which consume it.…”
Section: Discussionsupporting
confidence: 82%
“…Our results agree with Promya and Chitmant (2011) who reported that fingerlings which received feed 5% A. platensis+ basal diets had higher values for red and white blood cell counts and immunity stimulating capacity. The increase in red and white blood cells and immunity stimulating capacity due to the presence of C-phycocyanin in Spirulina, which can help build the immunity capacity (Vonshak, 1997b).Our results were in agreement with Qureshi et al (1996) who reported that Spirulina could stimulate the immune system via increasing the phagocytic and the natural killer activities and with Bermejo et al (2008) who reported that most antioxidant capacities of Spirulina protein extract are attributable to the biliproteins contained in this microalga, such as phycocyanin so that we can use Spirulina to improve the immunity capacity of the animals which consume it.…”
Section: Discussionsupporting
confidence: 82%
“…Based on the few existing studies, there are beneficial allergic and immunological effects of consumption of the blue-green algae Spirulina (Qureshi and Ali, 1996;. Recently calcium spirulan (Ca-Sp), a novel sulphated polysaccharide derived from Spirulina platensis, was shown to inhibit tumour invasion and metastasis (Mishima et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Qureshi and Ali 77 reported an increased phagocytic activity, increased antigen production and increased natural killer cell-mediated antitumor activity in chicken for the same cyanobacterium (Spirulina). In a preliminary small clinical study, an increase in 13.6-fold in interferon and 3-fold in interleukin (IL)-1b and -4 was observed in human blood cells incubated with Spirulina extracts.…”
Section: Immunomodulatory Activitymentioning
confidence: 99%